Analisis Kemampuan Pemecahan Masalah Peserta Didik Kelas IV SD Negeri Tawang Mas 01 dalam Menyelesaikan Soal Cerita Materi Diagram Batang Berdasarkan Gaya Belajar - Kurniatin, Yuni; Pramasdyahsari, Agnita Siska; Susilowati, Anis; Rahmawati, Noviana Dini (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to describe and determine students' abilities in solving mathematical problems with a focus on learning styles. The research subjects were Class IV students at SD Negeri Tawangmas. This research is a qualitative descriptive study which aims to determine and describe mathematical problem solving abilities in terms of students' learning styles. Data was collected using questionnaires, tests and interviews. The use of questionnaires describes visual learning styles, auditory and kinesthetic learning styles. Two test numbers determine the mathematical problem solving ability in the Polya step, and the interview confirms the mathematical problem solving ability. The data analysis techniques are reduction, presentation and verification. Based on the results, this study had 7 respondents with a bias towards visual style 3, auditory style 2 and kinestatic style with literacy skills from the results of the report cards, the average report card score was 76.28 and the standard deviation was 17.03. With problem-solving abilities for each style, namely 1) students with a visual style have the ability to understand problems, organize and carry out them and re-check the results of their work. 2) students with an auditory style have the ability to understand problems, organize and carry out them and review the results of their work. 3) students with an auditory style have the ability to understand problems, organize them, and are unable to carry them out until they are unable to recheck the results of their work.